Hemophilia is associated with accelerated biological aging - Marina Trappl; Rafaela Vostatek; Manuel Salzmann; Daniel Kraemmer; Johanna Gebhart; Philipp Hohensinner; Ingrid Pabinger; Cihan Ay (Haematologica)
Hemophilia is a rare X-linked bleeding disorder caused by mutations in the F8 or F9 gene (hemophilia A or B), leading to deficient factor VIII or IX proteins, respectively. Hemophilia-related complications caused by bleeding into the joints (the hallmark of hemophilia) and age-related comorbidities occur frequently and impact the functionality and quality of life of persons with hemophilia (PwH). Given the chronic nature of hemophilia, we hypothesized that hemophilia has an association with accelerated biological aging.